2009
DOI: 10.2298/jsc0911229b
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in the leaf surface composition of field grown grapevine plants

Abstract: The leaf surface is the first barrier of grapevine plants towards various environmental stressors causing damage in vineyards. For this reason, identification of leaf surface metabolites in grapevine and their putative role in plant-environment interactions is important for viticulture. In this study, the leaf surface components of 16 grapevine plants (Vitis vinifera) growing in an experimental vineyard were analyzed in two consecutive seasons -the summer and the autumn of 2007. Forty-eight individual metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…From the group of terpenes and terpenoids several have been detected in other studies, for example, E‐geraniol, 4‐ethenyl‐2‐methoxy‐phenol and eugenol by Wirth et al (), β‐limonene, β‐ionone and methyl salicylate by Tasin et al (), and β‐myrcene, β‐cyclocitral, E‐citral and allo‐ocimene by Rocha et al (). Batovska et al () also found nonadecane, hexahydrofarnesylacetone, phytol, dihydroactinoline, (2E)‐undecenal, nonanal and decanal in grapevine leaves. From the substance class of alcohols 2‐ethyl‐1‐hexanol, 1‐octanol and 1‐nonanol are reported, for example, by Canuti et al (), and benzenemethanol and benzeneethanol by Wirth et al ().…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…From the group of terpenes and terpenoids several have been detected in other studies, for example, E‐geraniol, 4‐ethenyl‐2‐methoxy‐phenol and eugenol by Wirth et al (), β‐limonene, β‐ionone and methyl salicylate by Tasin et al (), and β‐myrcene, β‐cyclocitral, E‐citral and allo‐ocimene by Rocha et al (). Batovska et al () also found nonadecane, hexahydrofarnesylacetone, phytol, dihydroactinoline, (2E)‐undecenal, nonanal and decanal in grapevine leaves. From the substance class of alcohols 2‐ethyl‐1‐hexanol, 1‐octanol and 1‐nonanol are reported, for example, by Canuti et al (), and benzenemethanol and benzeneethanol by Wirth et al ().…”
Section: Resultsmentioning
confidence: 92%
“…Most substances were identified by comparison of mass spectra and RI of authentic standards. Batovska et al () analysed liquid extracts of grapevine leaves and detected more than 125 metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Lebih lanjut, ekstrak daun cabai dari perlakuan kompos gulma siam, NPK, kotoran sapi dan kontrol juga mengandung senyawa dari golongan ester yaitu metil hexanoate dan metil octadec-9-enoate. Pada penelitian Batovska et al, (2009), metil hexadecanoat dan metil octadec-9-enoate memiliki peranan penting dalam komunikasi kimia antara tanaman dengan spesies serangga tertentu.…”
Section: Serapan N P Dan Kunclassified
“…The presence of alkyl alkanoates, terpenes, sterols, alkanals, alkanoic acids, ketones, hydrocarbons, and alkanols has been reported in leaves of Actinidia deliciosa (Celano et al, 2006). Batovska et al (2009) studied the leaf wax component of 16 grapevine plants (Vitis vinifera) in summer and autumn. The wax components present in leaves were aldehydes, hydrocarbons, terpenes, free and esterified fatty acids, alcohols, sterols, and ketones.…”
Section: Compositionmentioning
confidence: 99%